Rearing Conditions and Automated Feed Distribution Systems for Zebrafish (Danio rerio) - Gianmarco Del Vecchio; Aurora Mazzei; Roberta Schiavone; Ana S. Gomes; Giovanni Frangelli; Tommaso Sala; Stefania Fantino; Marco G. A. Brocca; Amilcare Barca; Ivar Rønnestad; Tiziano Verri (Applied Sciences, 2022)
Zebrafish (Danio rerio) is a well-established animal model, used in a number of research areas. In the last decade, it has also emerged as a tool to evaluate the effects of diets and dietary components and to test novel paradigms in nutrigenomics, nutrigenetics, and nutritional physiology. Despite its worldwide use, the standardization of the zebrafish rearing conditions, including daily nutritional and good feed management practices, is not yet achieved. This is surprising when compared with what is available for other reared animals, such as rodents or other (e.g., commercial) fishes. To date, a major applicative goal in zebrafish nutritional physiology research is to define common, standard, and reproducible protocols of rearing and feeding conditions to generate reliable and comparable results among research laboratories. This review aims to focus on limitations and disadvantages of the current rearing and feeding practices and on some recent technological solutions provided by research groups and/or biotech companies in the field of facility design, with emphasis on automated feeding distribution systems. A general overview of some common schemes of zebrafish husbandry is also given.